2020
DOI: 10.1097/shk.0000000000001351
|View full text |Cite
|
Sign up to set email alerts
|

TUDCA Ameliorates Liver Injury Via Activation of SIRT1–FXR Signaling in a Rat Hemorrhagic Shock Model

Abstract: Objective: The aim of this study was to investigate the changes of bile acids in the liver during hemorrhagic shock (HS) and their potential to attenuate liver injury via activation of SIRT1 (sirtuin 1)–FXR (farnesoid X receptor) signaling. Methods: A Sprague–Dawley (SD) rat HS model was established, whereas HepG2 cells were hypoxically cultured to simulate HS in vitro. Liver bile acids (BA) were profiled with ultraperformance liquid chromatography-tand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…TUDCA/UDCA has been used in Chinese medicine for centuries, and hundreds of studies have already underscored its beneficial effects in the treatment of many pathological conditions. Nevertheless, TUDCA is constantly a very intriguing pharmacological agent and a growing number of pre-clinical and clinical research is still performed, unraveling novel aspects of TUDCA functioning [94,[182][183][184][185][186][187]. Although through the years this bile acid has been demonstrated to be a very efficient hepatoprotectant and ER stress alleviator, many innovative contemporary reports inform about its novel potential applications and molecular modes of action.…”
Section: Therapeutic Perspectives and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…TUDCA/UDCA has been used in Chinese medicine for centuries, and hundreds of studies have already underscored its beneficial effects in the treatment of many pathological conditions. Nevertheless, TUDCA is constantly a very intriguing pharmacological agent and a growing number of pre-clinical and clinical research is still performed, unraveling novel aspects of TUDCA functioning [94,[182][183][184][185][186][187]. Although through the years this bile acid has been demonstrated to be a very efficient hepatoprotectant and ER stress alleviator, many innovative contemporary reports inform about its novel potential applications and molecular modes of action.…”
Section: Therapeutic Perspectives and Limitationsmentioning
confidence: 99%
“…Interestingly, TUDCA-dependent inhibition of class I and II HDAC enzymes restored the expression GLUT4, resulting in improvement of insulin sensitivity and glucose tolerance [189]. Moreover, TUDCA has been found to modify the expression of sirtuins, which are NAD-dependent deacetylases responsible for removing acetyl groups from many histone and non-histone proteins [185,190]. Thus, TUDCA decreased ethanol-induced overexpression of sirtuin-2 [190] and restored hypoxia-and hemorrhagic shock-induced down-regulation of sirtuin-1 [185].…”
Section: Therapeutic Perspectives and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This general increase disqualifies the total amount of bile acids in serum as a biomarker to differentiate between disease states but might suit to estimate a liver involvement early on. However, it clearly shows that the liver and especially the bile are affected in all critically ill patients at a rather early point during the course of the disease, a finding that has been described before [22]. This finding is in strong contrast to perceived regular clinical practice where secondary liver injury is a late, often additionally found, and frequently final disease state following a (long) course of critical illness.…”
Section: Discussionmentioning
confidence: 57%
“…It has previously been reported that activation of Sirt1 decreased the production of several pro-inflammatory cytokines, including TNF-a, IL-12, and IL-18 in EIC rats and protected syncytiotrophoblasts against TCA-induced inflammatory injury through the Sirt1-NF-kB signaling pathway (Liao et al, 2018). Moreover, NF-kB is a downstream gene of FXR, and upregulating Sirt1/FXR/NF-kB signaling had an efficient protective effect on rats from hemorrhagic shock induced liver injury by decreasing inflammatory responses (Zhang et al, 2017;Sun et al, 2019;Yu et al, 2019). Thus, we hypothesized that activation of FXR by baicalin through the Sirt1/HNF-1a signaling pathway might also play a key role in regulating the NF-kB pathway, which would need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%